Pemanfaatan Teknologi Nanobubble untuk Produksi Anguilla sp pada Era Society 5.0 - Aulia Marwah Paradhiba; Farisa Febriyanti; Ella Rahmadania; Fazila Yanisa; Fitria Ulfa Adelina; Retno Cahya Mukti (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Paradhiba AM, Febriyanti F, Rahmadania E, Yanisa F, Adelina FU, Mukti RC. 2021. Utilization of nanobubble technology for the production of anguilla sp in era society 5.0. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 435-444. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Eel fish species (Anguilla sp) is a fish commodity that has high economic value. Eel cultivation is still not widely controlled because of many factors that influence it, especially water quality conditions. Nanobubble technology is a technology that can maintain water quality, especially to increase oxygen in water. This study aimed to increase the production of eel fish through the nanobubble technology system and to improve the community's economic system in the fisheries sector. The writing method in this study used the literature study method. The results of the study explained that nanobubble technology was able to produce nano-sized air bubbles (70–200 nm) and rich in oxygen so that it could increase dissolved oxygen levels to 9 mg/L. Dissolved oxygen was needed to increase oxidation so that the nitrification process could take place so that it could eliminate ammonia levels in the water. In addition, the high oxygen content could increase metabolism so that it could increase the growth of eel fish. Dissolved oxygen concentration of water was a key control of habitat quality and a critical measure of water health for eel survival Therefore, with the nanobubble technology, it is expected to increase the production of eel fish. Advice for the public could be used nanobubble technology in the process of eel fish farming so that the production obtained could be maximized.